Influence of Hydrocolloids on Lipid Digestion and Vitamin D Bioaccessibility of Emulsion-Filled Soft Gels - (:unkn) unknown (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The global increase in the older population presents a nutritional challenge; therefore, the development of food products for this group must take into account the physiological changes associated with aging. This work aimed to evaluate the effects of droplet size, conventional emulsion (CE) and nanoemulsion (NE), and different hydrocolloids, soy protein (SPI), whey protein (WPI), agar (AG), and kappa-carrageenan (CAR), on the physical properties, lipid digestibility, and bioaccessibility of emulsion-based gels enriched with vitamin D. The main findings indicated that all gels exhibited non-Newtonian behavior and suitable viscosity and texture for the swallowing needs of older people. The highest release of free fatty acids (similar to 30%) was observed in the NE + WPI sample, independent of droplet size. Instead, SPI gels showed the highest vitamin D bioaccessibility, likely due to their less-structured gel network. Thus, gels containing WPI + AG provide a favorable balance between an easy-to-swallow texture and efficient nutrient release, making them suitable for producing food based on emulsion-filled gels with good physical and nutritional properties. Hence, these results highlight the potential of tailored hydrocolloid combinations to develop nutrient-fortified and texture-appropriate gels that address the nutritional needs of the older population.